Effects of corn particle size and diet form on finishing pig growth performance and carcass characteristics - Jeremiah E Nemechek; Michael D Tokach; Kyle F Coble; Joel M DeRouchey; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2013)
A total of 960 pigs (PIC TR4 × Fast Genetics York-AND × PIC Line 02, initially 75.7 lb BW) were used in a 101-d trial to determine the effect of corn particle size and diet form on finishing pig growth performance and carcass characteristics. Pens were randomly allotted to 1 of 6 experimental treatments by initial BW with 8 pens per treatment and 20 pigs per pen. All diets were fed in four phases with the same cornsoybean meal—based diet containing 30% dried distillers grains with solubles (DDGS; Phases 1 to 3) or 15% DDGS (Phase 4) used for all diets. The 6 experimental treatments were arranged in a 2 × 3 factorial with main effects of final feed form (meal vs. pellet) and corn particle size (650 Î¼, 350 Î¼, or an equal blend of the 650 Î¼ and 350 Î¼ ground corn). Overall (d 0 to 101), linear particle size × diet form interactions were observed (P<0.02) for ADFI and F/G due to ADFI decreasing and F/G improving as particle size was reduced for pigs fed meal diets but not for pigs fed pelleted diets. Pigs fed pelleted diets had increased (P<0.001) ADG and final BW and improved (P<0.001) F/G. As corn particle size decreased, ADG and ADFI decreased (P<0.02) linearly. Pigs fed pelleted diets had increased (P<0.001) HCW compared with pigs fed meal diets. Yield, backfat, and loin depth were not influenced by particle size or diet form. In summary, pigs fed pelleted diets had improved growth performance compared with those fed meal diets, with the greatest improvement in F/G observed from pigs fed coarse-ground (650 Î¼) corn. Feed efficiency improved as corn particle size decreased for pigs fed meal diets but not for those fed pelleted diets, suggesting that there was no benefit to grinding corn finer than 650 Î¼ for pelleted diets.; Swine Day, Manhattan, KS, November 21, 2013
Keywords: Swine day; 2013; Kansas Agricultural Experiment Station contribution; no. 14-044-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1092; Finishing pig; Particle size; Pelleting